An adjoint approach to identification in electromyography: modeling and first order optimality conditions. (26th November 2021) - Sproll, Tobias; Schiela, Anton
Abstract: In medical treatment it can be necessary to know the position of a motor unit in a muscle. Recent advances in high-density surface electromyography (EMG) measurement have opened the possibility of extracting information about single motor units. We present a mathematical approach to identify these motor units. On the base of an electrostatic forward model, we introduce an adjoint approach to efficiently simulate a surface EMG measurement and an optimal control approach to identify these motor units. We show basic results on existence of solutions and first-order optimality conditions.